Localization Efforts and Sustainable Development; Illusion of Purchasing Technology and Technology of Selling Illusion - المنصوري , عبد الجليل; الكيخيا, فيصل; الساعدي , محمد (Dirasat in Economics and Business, 2015)
Not so long ago, the concept of technology was adjacent to the word "industry" or "automation", hence, new concept has been spread known as "Transfer of Technology" with assumption that it is quite possible to be transferred and purchased. People got amazed with this panacea called "High Technology" and the "Relevant Technology" that has been used by India people and ignored by so many others. Since we are using this technology concept with wrong relevancy or utilizing it with different meanings, and we associate it strongly with development efforts, it is very important to determine exactly what technology concept is all about. If industry means manufacturing machines and tools, and automation deals with utilization of machines and tools in order to operate each other's. So, what is meant by technology? In order to understand it then to upgrade its utilization. The article pinpoints that habits can be understood as an "internal tactics" to gain saving in mental or biological effort. In computer language, it is sort of "Firmware" or "Default" to assure virtual response that does not consume so much time. The machine that man manufacture is separate from him , it could be called "External technology" for saving efforts, thus the machine could be considered as an external continuum to a human response for the environment. Since the routine steps are built in when designing the machine, then the machine is no longer just a tangible thing, rather it is an "Embedded Knowledge". Therefore, this article explains the meaning of knowledge economy, knowledge organization, knowledge management, knowledge workers, human capital, scientific society and learning organization, in order to achieve a recovered mental capacity.